2005
DOI: 10.1111/j.1440-1754.2005.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Prone or supine for infants with chronic lung disease at neonatal discharge?

Abstract: The supine position appears appropriate for very preterm infants with CLD going home from the neonatal unit. Respiratory instability on neonatal discharge is more likely to be associated with immaturity than CLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
15
1
3
Order By: Relevance
“…This is in agreement with the findings of some authors, 14,15,18 but contrasts with the results observed in other studies, which have demonstrated significant improvements in SpO 2 in preterm newborn infants put in the prone position. 7,8,19 The samples in those studies were composed of newborn infants on mechanical ventilation, or, in the majority, of oxygen-dependent newborn infants.…”
Section: Variables Analyzedcontrasting
confidence: 57%
“…This is in agreement with the findings of some authors, 14,15,18 but contrasts with the results observed in other studies, which have demonstrated significant improvements in SpO 2 in preterm newborn infants put in the prone position. 7,8,19 The samples in those studies were composed of newborn infants on mechanical ventilation, or, in the majority, of oxygen-dependent newborn infants.…”
Section: Variables Analyzedcontrasting
confidence: 57%
“…Isso corrobora os achados de alguns autores 14,15,18 e difere dos resultados observados em outros estudos, que demonstraram melhora significativa da SpO 2 em recém-nascidos pré-termo na posição prona 7,8,19 . As amostras desses estudos eram constituídas por recém-nascidos em ventilação mecânica ou, em sua maioria, por recém-nascidos em dependência de oxigênio.…”
Section: Peso Nounclassified
“…When the previous survey was conducted, there were few data on the effects of the sleeping position in prematurely born convalescent infants. The data available suggested that the prone position, when compared to the supine position in such infants, had advantages: lower apnoea density and less periodic breathing [9], better response to hypercapnia [10] and superior oxygenation [8]. Such data may have influenced practitioners and hence they did not discourage prone sleeping.…”
Section: Discussionmentioning
confidence: 99%